Clinical and Ultrastructural Skin Alterations in the Ehlers-Danlos Syndrome, Hypermobility Type - Trinh Hermanns-Lê; Gérald E. Piérard; Daniel Manicourt; Claudine Piérard-Franchimont (Dermatology, 2016)
Ehlers-Danlos Syndrome (EDS) represents a cluster of specific genetic connective tissue disorders. It is clinically evoked when skin appears velvety and hyperextensible, in combination with joint laxity and connective tissue fragility. The hypermobile variant (EDSH) is among the most common presentations. It presents as an autosomal dominant pathology. The genetic mutation presently remains undisclosed in most cases. However, ultrastructural alterations are often distinguishable. Ehlers-Danlos Syndrome Hypermobile (EDSH) is mostly observed in women in whom additional signs to joint laxity are present. Hyperextensibility and/or velvety presentation of skin is one of the two major diagnostic signs in EDSH. Atrophic scars and delayed wound healing are commonly present. These features have to be considered in particular by plastic surgeons. The ultrastructural skin changes show various numbers of flower-like collagen fibres as well as other abnormalities in the connective tissue components.